ChemInform Abstract: Biotransformation of Aromatic Ketones and Ketoesters with the Non‐Conventional Yeast Pichia glucozyma. Issue 17 (April 2015) - Contente, Martina Letizia; Molinari, Francesco; Zambelli, Paolo; De Vitis, Valerio; Gandolfi, Raffaella; Pinto, Andrea; Romano, Diego
Abstract The concurrent activity of ketoreductase and esterase of the yeast Pichia glycozyma allows the reduction of ketones and β‐ketoesters to give hydroxyesters, hydroxy acids, or lactones as products.